The role of artificial intelligence personalisation in e-commerce: Customer purchase decisions in the retail sector - Kebashnee Moodley; Lavina Sookhdeo (South African Journal of Information Management)
Background: Online shopping in South Africa grew significantly during the pandemic, highlighting its potential across income groups. Leveraging artificial intelligence (AI) is crucial for e-commerce businesses to enhance customer experiences and stay competitive in the digital age.